Treasure Island - Stevenson, Robert louis (Karachi : Oxford university press, 2019)
"Treasure Island" by Robert Louis Stevenson is an adventure novel about a young boy named Jim Hawkins, who discovers a treasure map. He joins an expedition to find the hidden treasure on a mysterious island. Onboard the ship Hispaniola, Jim befriends the cook, Long John Silver, who is revealed to be a pirate leader planning to steal the treasure. Jim and the loyal crew face various challenges, including battles with the pirates, before ultimately finding the treasure. The novel explores themes of loyalty, betrayal, and adventure.
Keywords: English : Novel